Biotechnology law : a primer for scientists - Morrison, Alan J. (Columbia University Press, 2020)
"The biotechnology industry and the law are inextricable. Patent, regulatory, and contract law profoundly shape this industry, and each of these practice areas is deeply intertwined with the science it governs. Yet many in the biotech industry lack even a basic grasp of these laws, jeopardizing their business success as a result. This book is an essential introduction to biotechnology law for startup founders, regulatory specialists, patent liaisons, investors, academics, students, and other non-attorneys with biotech backgrounds. It covers core topics such as patentability, patent prosecution and infringement, patent opinions, the development and FDA approval of small molecule and biologic drugs, regulatory exclusivity, generic drugs and ANDA litigation, biosimilars and the patent dance, patent licenses, and collaboration agreements. Biotechnology Law is a clear, concise, and entirely practical primer on the topic, replete with straightforward, real-world examples to illustrate each key concept. The author's expert treatment embraces the new reality that understanding the legal machinery through which science becomes business is not a luxury-it is a crucial part of a scientist's training. Alan J. Morrison is a lecturer in the Department of Biological Sciences at Columbia University. He practices biotechnology law in New York City"--